Enhancing Cultural Literacy in Elementary Students: The Impact of the STAD Cooperative Learning Model - Kurnianti, Dwi Inda; Erlisnawati, Erlisnawati; Syahrilfuddin, Syahrilfuddin (AL-ISHLAH: Jurnal Pendidikan, 2024)
This study investigates the impact of the Student Teams-Achievement Divisions (STAD) cooperative learning model on the cultural literacy skills of fourth-grade students at SDN 183 Pekanbaru. With growing emphasis on cultural literacy in education, it is essential to evaluate effective pedagogical approaches, such as cooperative learning, that may enhance these skills. A quantitative approach was used with a quasi-experimental design, employing a non-equivalent control group format. Simple random sampling selected 50 students, with 25 placed in the experimental group (class IV D) and 25 in the control group (class IV A). Data were collected using pretests, posttests, and cultural literacy questionnaires. Analysis was performed using IBM SPSS Statistics 24, with hypothesis testing conducted through an independent sample t-test. The hypothesis test showed no significant difference in cultural literacy skills between the experimental and control groups. The independent t-test yielded a significance value of 0.828 (p 0.05), leading to the acceptance of the null hypothesis (H0) and rejection of the alternative hypothesis (Ha). Furthermore, the n-gain test in the experimental group indicated a mean score of 0.23 (≤ 0.3), suggesting the STAD model contributed to a 23% improvement in cultural literacy skills. Although the STAD cooperative learning model demonstrated only a modest influence on students’ cultural literacy, the 23% improvement is meaningful given the study's constraints. This suggests that STAD has potential but requires further investigation under varying conditions. The STAD cooperative learning model has a limited but noteworthy effect on enhancing students' cultural literacy, warranting additional research to explore its full potential.